2022
DOI: 10.1155/2022/2293473
|View full text |Cite|
|
Sign up to set email alerts
|

Production Scheduling Optimization of Garment Intelligent Manufacturing System Based on Big Data

Abstract: In order to improve the efficiency of cloth laying and cutting integrated production process, this article proposes a method of optimal scheduling of cloth laying and cutting garment production system process based on big data and genetic algorithm. The chromosomes in the algorithm are expressed by real strings. The method of bit string crossover and mutation is used to solve the premature problem of the algorithm. The experimental results show that the actual cutting time of the plan is 736 min, and the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…However, it has been noted that the SMMEs in this industry frequently struggle with innovation due to their lack of education as running a small business requires little to know formal education. (Sun and Cao, 2022) concur, stating that despite the important role that the clothing industry plays in China's economic growth, many apparel manufacturers still stick to traditional business methods, thereby failing to optimise their processes and progress as they should. This serves to exacerbate problems with competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it has been noted that the SMMEs in this industry frequently struggle with innovation due to their lack of education as running a small business requires little to know formal education. (Sun and Cao, 2022) concur, stating that despite the important role that the clothing industry plays in China's economic growth, many apparel manufacturers still stick to traditional business methods, thereby failing to optimise their processes and progress as they should. This serves to exacerbate problems with competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%